THE ROLE OF NEUROMARKETING IN SHAPING CONSUMER BEHAVIOR: HOW BUSINESSES ARE USING SCIENCE TO DRIVE SALES (Al-Aasar, 2025)
This study aims to explore the impact of neuromarketing techniques on consumer behavior and business success, focusing on how companies in Pakistan utilize scientific insights to drive sales and enhance brand engagement. The research investigates the strategies businesses employ to leverage neuromarketing, while addressing the challenges and barriers they face in implementing these techniques. Using a qualitative research method, data is collected through interviews, case studies, and surveys with marketing professionals, neuromarketing experts, and business leaders across various industries, including retail, FMCG, and e-commerce. The findings highlight that businesses employing neuromarketing techniques, such as emotional appeals, sensory marketing, and personalized advertising, are better positioned to improve customer loyalty, brand perception, and profitability. The businesses that fail to effectively incorporate neuromarketing strategies risk losing consumer trust, damaging their reputation, and losing market share. This study provides insights into the growing role of neuromarketing in shaping consumer behavior and its potential to drive business success.